1996
DOI: 10.2307/2963492
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Plant Species Control Over Litter Decomposition in Alaskan Tundra

Abstract: I compared effects of increased temperature and litter from different Alaskan tundra plant species on cycling of carbon and nitrogen through litter and soil in microcosms. Warming between 4° and 10°C significantly increased rates of soil and litter respiration, litter decomposition, litter nitrogen release, and soil net nitrogen mineralization. Thus, future warming will directly increase rates of carbon and nitrogen cycling through litter and soil in tundra. In addition, differences among species' litter in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
800
11
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 859 publications
(862 citation statements)
references
References 71 publications
47
800
11
4
Order By: Relevance
“…In addition, k values of vascular plant litter in peatlands were positively related with both the mean annual temperature (Pearson's r = 0.37; p < 0.001; n = 69) and the mean total annual precipitation (Pearson's r = 0.39; p < 0.001; n = 69), whereas the k values of Sphagnum litter were not correlated to either of these climatic factors. Increased decomposition rates of vascular plant litter in peatlands with increasing temperature were also reported by other authors [Hobbie, 1996;Thormann et al, 2004;Moore et al, 2005;Breeuwer et al, 2008]. Furthermore, many laboratory and field experiments have shown that higher temperature resulted in increasing decomposition of vascular plant and Latter and Cragg [1967], Rochefort et al [1990], Johnson and Damman [1991], Gallardo and Merino [1993], Aerts and De Caluwe [1997], Foote and Reynolds [1997], Wrubleski et al [1997], Latter et al [1998] …”
Section: Climatementioning
confidence: 55%
“…In addition, k values of vascular plant litter in peatlands were positively related with both the mean annual temperature (Pearson's r = 0.37; p < 0.001; n = 69) and the mean total annual precipitation (Pearson's r = 0.39; p < 0.001; n = 69), whereas the k values of Sphagnum litter were not correlated to either of these climatic factors. Increased decomposition rates of vascular plant litter in peatlands with increasing temperature were also reported by other authors [Hobbie, 1996;Thormann et al, 2004;Moore et al, 2005;Breeuwer et al, 2008]. Furthermore, many laboratory and field experiments have shown that higher temperature resulted in increasing decomposition of vascular plant and Latter and Cragg [1967], Rochefort et al [1990], Johnson and Damman [1991], Gallardo and Merino [1993], Aerts and De Caluwe [1997], Foote and Reynolds [1997], Wrubleski et al [1997], Latter et al [1998] …”
Section: Climatementioning
confidence: 55%
“…Generally speaking, the decomposition rate of litter increases with temperature. However, enzymes involved in the breakdown of complex, recalcitrant C substrates appear to be more sensitive to temperature than those involved in breakdown of labile substrates (O'Connell, 1990;Hobbie, 1996;Fierer et al, 2005). This sensitivity is due to the enzyme kinetics; more complex substrates require higher activation energies than less complex substrates (Fierer et al, 2005).…”
Section: Decomposer Communities and Extracellular Enzyme Productionmentioning
confidence: 95%
“…Soil moisture exerts a control on tundra ecophysiology through production, decomposition and nutrient cycling (Miller et al 1984), and a lowered water-table and increased thaw might be expected to accelerate the rate of soil decomposition (CO 2 source) over photosynthesis (CO 2 sink), so that the balance in tundra soils shifts from one of C-input, or storage, to C-output (Billings et al 1982(Billings et al , 1983Johnson et al 1996). If the effect of decomposition were to increase nutrient availability, there may be an additional uptake of CO 2 owing to higher rates of photosynthesis (Shaver & Chapin 1986;Shaver et al 1998;Johnson et al 2000), although as sink strength in vascular plants decreases, productivity may be offset by substrate-controlled or nutrient-limited CO 2 loss from soil respiration by microorganisms (Nadelhoffer et al 1991;Hobbie 1996;Jonasson et al 1999). Larger sinks of CO 2 are accordingly associated with lower respiration rates in wetter habitats (Vourtilis et al 2000), while short-term experiments designed to explain the net effect of climate warming on soil moisture and the C-balance of tundra plots (Johnson et al 1996) support observational data demonstrating that a shift from net C-input to C-output accompanies the recent drying of tundra habitats (Oechel et al 1993Weller et al 1995).…”
Section:      mentioning
confidence: 99%